Optimizing the Use of Working Capital in an Effort to Increase Company Profitability - Dirmansyah Darwin; Soni Suardi; Salim Diarra; Moses Soediro; Ivana Grasielda (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2024)
This research aims to determine the optimization of the use of working capital in an effort to increase company profitability at PT. Semen Indonesia (Persero) Tbk. This research is quantitative descriptive. The population in this research is the financial statements of PT. Semen Indonesia (Persero) Tbk, and the sample for this research is the financial report of PT. Semen Indonesia (Persero) Tbk for the 2019-2023 period. The data collection technique used is financial ratios, namely liquidity ratios using the current ratio, activity ratios using working capital turnover, and profitability ratios using Net Profit Margin (NPM). The research results show that efficient use of working capital can increase company profitability. The results of data analysis from the assessment of each ratio can be concluded that the liquidity ratio using the current ratio calculation can be said to be quite good during the 2019-2023 period. The activity ratio using working capital turnover calculations is said to be good during the 2019-2021 period, but in the 2022-2023 period the activity ratio is categorized as not good. Profitability ratios using NPM obtained fluctuating results during the 2019-2023 period. The company's NPM in 2019-2021 was efficient, but in 2022-2023 the company's NPM was categorized as inefficient.